2018
DOI: 10.2147/ndt.s160060
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric-onset multiple sclerosis in Egypt: a multi-center registry of 186 patients

Abstract: IntroductionAlthough the frequency of pediatric-onset multiple sclerosis (POMS) has increased in recent decades, it is still highly uncommon, which creates a need for the involvement of more registries from various clinical centers.ObjectiveTo characterize the demographic, clinical, and paraclinical features of Egyptian patients with POMS.Patients and methodsA retrospective chart review study was undertaken on 237 Egyptian patients with demyelinating events which started before the age of 18 years who attended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…This study assessed the records of 21 patients. A discrete female predominance was observed (1.1:1), slightly lower than reported in other studies, 3,4,[18][19][20][21] as well as a mean age at diagnosis in agreement with previous studies (14.8 years). 18,19 Fourteen percent of patients had a family history of other AIDs, but not of MS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study assessed the records of 21 patients. A discrete female predominance was observed (1.1:1), slightly lower than reported in other studies, 3,4,[18][19][20][21] as well as a mean age at diagnosis in agreement with previous studies (14.8 years). 18,19 Fourteen percent of patients had a family history of other AIDs, but not of MS.…”
Section: Discussionsupporting
confidence: 92%
“…Although uncommon, it is possible to have positive anti-MOG antibodies in MS. 3 In the present study, the mean time between the first MS manifestation and diagnosis was 2.8 months, similar to one study 18 but lower than reported in others. [19][20][21] Despite the small number of patients included, using the revised 2017 McDonald criteria apparently enabled earlier diagnosis and treatment. Other studies, both before and after 2017, reported a longer mean time until diagnosis than reported in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Relapses of the disease in all patients were treated with high doses of corticosteroids for 3–5 days and 66.7% of them continued with corticosteroid therapy using decreasing doses after day 5. Our results correspond to other studies that reported treatment with high doses of corticosteroids and continuation with corticosteroid therapy at decreasing doses [ 42 , 43 ]. Plasma therapeutic replacement was administered after the ineffectiveness of high doses of corticosteroids, with relatively good outcome.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, fingolimod also significantly delayed time to first relapse and 3-month confirmed disability worsening. Effects reported from the clinical trial were echoed in the limited number of previously published observational studies involving fingolimod in POMS 1921…”
Section: Discussionmentioning
confidence: 99%
“…Most recently Egyptian registry data of 186 POMS patients were published by Hamdy et al in 2018 21. In this registry, there were a total of 8 patients treated with fingolimod (3 treated within 1 year of symptom onset and 6 treated after more than a year of symptoms since onset).…”
Section: Fingolimod Experience In Pomsmentioning
confidence: 99%